Fazendo arte com as cores - Henrique, Maria de Fatima Oliveira; Firmino, Valéria Aparecida; Felício, Marli; Silvério, Agda Rodrigues Rios; Lima, Eliene Xavier de; Oliveira, Maria Auxiliadora de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf